Climate Change and Environmental Law: The Indonesian Court’s Role in Enforcing Sustainable Development (Indonesian Court and Justice Review, 2025)
As climate change intensifies environmental degradation in Indonesia, courts are increasingly called upon to adjudicate disputes involving ecological harm, regulatory compliance, and government accountability. This study examines the role of Indonesian courts in promoting sustainable development through environmental law enforcement, with a focus on recent landmark decisions involving deforestation, pollution, and climate-related litigation. Using a combination of doctrinal analysis and case review, the research assesses how judicial bodies interpret environmental protection laws, apply the precautionary and intergenerational equity principles, and balance environmental concerns with economic development agendas. The findings demonstrate that courts have occasionally issued progressive rulings—holding corporations and government agencies accountable—but enforcement remains uneven due to legal ambiguities, lack of technical expertise, and institutional limitations. The novelty of this study lies in its analysis of climate-related jurisprudence within a developing country context, offering insights into how judicial activism can contribute to environmental governance. The research also identifies structural barriers that hinder judicial effectiveness, including limited access to environmental evidence, procedural hurdles, and weak implementation mechanisms. It concludes by proposing reforms to enhance the judiciary’s capacity in climate adjudication and strengthen legal frameworks for environmental protection in Indonesia.